Representasi Pria Metroseksual dalam Iklan Barenbliss Bloom My Way With Gabriel Prince - Awendsa Urfatunnisa Tasyaul Mu'izzah; Talfi Jannati; Faruq Alhasbi (Pawarta: Journal of Communication and Da'wah, 2024)
This research motivated by the phenomenon of men using cosmetic products. Therefore, this research aimed to determine the representation of metrosexual men in the Barenbliss Bloom My Way with Gabriel Prince advertisement. Metrosexual men are men who prioritize physical appearance by wearing cosmetic products and fashionable clothing. Metrosexual men have bright and clean faces. Currently, metrosexual men like to take care of their body parts, especially their faces, to make them look more attractive. Roland Barthes' semiotic theory used to understand the meaning of denotation, connotation and myth. This research uses a semiotic approach with descriptive qualitative methods. The data in this research is supported by documentation in the form of still images related to metrosexual men in the Barenbliss Bloom My Way with Gabriel Prince advertisement. The analysis results carried out, the narrative of events and scenes clearly shows the elements of the representation of metrosexual men which can be seen from the make-up, gestures, characters, settings and costumes in the advertisement.